Multiple bradykinin-related peptlides from the capture web of the spider Nephila clavipes (Araneae, Tetragnatidae) - Volsi, ECFR; Mendes, M. A.; Marques, M. R.; dos Santos, L. D.; Santos, K. S.; de Souza, B. M.; Babieri, E. F.; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2006)
Three bradykinin-related peptides (nephilakinins-I to -III) and bradykinin itself were isolated from the aqueous washing extract of the capture web of the spider Nephila clavipes by gel permeation chromatography on a Sephacryl S-100 column, followed by chromatography in a Hi-Trap Sephadex-G25 Superfine column. The novel peptides occur-red in low concentrations and were sequenced through ESI-MS/MS analysis: nephilakinin-I (G-P-N-P-G-F-S-P-F-R-NH2), nephilakinin-Il (E-A-P-P-G-F-S-P-F-R-NH2) and nephilakinin-III (P-S-P-P-G-F-S-P-F-R-NH2)- Synthetic peptides replicated the novel bradykinin-related peptides, which were submitted to biological characterizations. Nephilakinins were shown to cause constriction on isolated rat ileum preparations and relaxation on rat duodenum muscle preparations at amounts higher than bradykinin; apparently these peptides constitute B-2-type agonists of ileal and duodenal smooth muscles. All peptides including the bradykinin were moderately lethal to honeybees. These bradykinin peptides may be related to the predation of insects by the webs of N. clauipes. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: spider toxins; bradykinin-related peptides; muscle contraction/relaxation; mass spectrometrypeptide sequencing; peptide synthesis